High-order-harmonic generation from Rydberg atoms driven by plasmon-enhanced laser fields - (:unkn) unknown (AMER PHYSICAL SOC, 2016)
We theoretically investigate high-order-harmonic generation (HHG) in Rydberg atoms driven by spatially inhomogeneous laser fields, induced, for instance, by plasmonic enhancement. It is well known that the laser intensity should exceed a certain threshold in order to stimulate HHG when noble gas atoms in their ground state are used as an active medium. One way to enhance the coherent light coming from a conventional laser oscillator is to take advantage of the amplification obtained by the so-called surface plasmon polaritons, created when a low-intensity laser field is focused onto a metallic nanostructure. The main limitation of this scheme is the low damage threshold of the materials employed in the nanostructure engineering. In this work we propose the use of Rydberg atoms, driven by spatially inhomogeneous, plasmon-enhanced laser fields, for HHG. We exhaustively discuss the behavior and efficiency of these systems in the generation of coherent harmonic emission. Toward this aim we numerically solve the time-dependent Schrodinger equation for an atom, with an electron initially in a highly excited nth Rydberg state, located in the vicinity of a metallic nanostructure. In this zone the electric field changes spatially on scales relevant for the dynamics of the laser-ionized electron. We first use a one-dimensional model to investigate systematically the phenomena. We then employ a more realistic situation, in which the interaction of a plasmon-enhanced laser field with a three-dimensional hydrogen atom is modeled. We discuss the scaling of the relevant input parameters with the principal quantum number n of the Rydberg state in question and demonstrate that harmonic emission can be achieved from Rydberg atoms well below the damage threshold, thus without deterioration of the geometry and properties of the metallic nanostructure.
Keywords: EXTREME-ULTRAVIOLET; COHERENT SUPERPOSITION; ADIABATIC PASSAGE; IONIZATION; INTENSITY; RESONANCE; STATES; NANOSTRUCTURES; PHOTOEMISSION; RADIATION